Pulmonary embolism in patients with cancer: An updated and operative guide for diagnosis and management. (1st July 2022) - Tirandi, Amedeo; Preda, Alberto; Carbone, Federico; Montecucco, Fabrizio; Liberale, Luca
Abstract: Cancer-associated venous thromboembolism (VTE) is a leading cause of morbidity and mortality in patients with cancer. Appropriate risk stratification for primary and secondary VTE prevention as well as for risk of early death in acute setting is needed for an adequate treatment. Despite enormous advances have been made in the management of VTE in the last two decades, optimal medical therapy remains a major concern due to still high incidence of both symptomatic and incidental pulmonary embolism (PE), its recurrence, poor survival rate, bleeding risk and multiple drugs interactions. Novel oral anticoagulants (NOACs) simplified the treatment of VTE as compared to low-molecular-weight heparin (LMWH) due to their oral administration, fixed dose regimens and lower cost. However, their prescription requires extra caution, especially in patients with gastrointestinal malignancies. Lastly, data on reperfusion approaches remain confined to case series and subgroups analysis. The aim of this review is to summarize recent knowledge concerning PE in patients with malignancies, focusing on available treatments and decision making. Highlights: Venous thromboembolism is a leading cause of morbidity and mortality in patients with cancer. Pulmonary embolism during cancer carries risk of recurrence, bleeding and drug interactions. NOACs simplified the therapy of embolic episodes during cancer but require caution. Further studies are required to improve risk stratification tools.